Contrast in Tuvan Proverbs - Bochina, Tatyana G. (The New Research of Tuva, 2022)
The article examines a variety of practical realizations that the principle of contrast finds in Tuvan proverbs and sayings. Contrast is a universal method of cognition and of dichotomical structuring of the world. We focus on the role played by parallel constructions (making use of similarities or contrasts) in rhythmic and compositional ordering of Tuvan paremies. As it happens, in many other languages, they tend to take the form of syntactically symmetrical sentences, with opposing contradistinctions alternating rhythmically, which in turn sets the background for contrast.Special attention has been paid to classifying the oppositions. We have proved that Tuvan proverbs make use of a rich variety of lexical means of expressing contrast. In accordance with the field theory, they can be subdivided into the nuclear, central and peripheral zones, depending on how linguistically representative the unit is. Antonyms and converse terms appear at the core, as well as affirmative/negative oppositions, while the semantically and grammatically asymmetrical quasi-antonyms, and quasi-converse terms and co-hyponyms comprise the centre. Finally, connotative antonyms move to the periphery.The contrasted pairs of units are analysed against the background of how they reflect the linguistic world picture, dealing with a number of cultural codes, including the zoomorphic, somatic and anthropomorphic ones. The case of Tuvan proverbs containing zoonyms, somatic words and/or kinship terms is a good example of how archetypical oppositional invariants come together with the ethnic variegation of their expression.The article also pays attention to axiological nature of how the world is perceived and described in a binary fashion, and to the qualitative and quantitative assessment and the role it plays in setting up proverbial binomiality.Empirically, our study is limited to 770 proverbs from the 2020 collection brought together by K. Budup. Continuous sampling helped us select a number of contrast-based paremies from this batch.
Keywords: paremy; contrast; cultural code; Tuvan proverbs; Tuvan language; parallelism; opposition